MR Imaging of the Superior Profile of the Midbrain: Differential Diagnosis between Progressive Supranuclear Palsy and Parkinson Disease - Righini, Andrea (AJNR Am J Neuroradiol, 2004)
BACKGROUND AND PURPOSE: Quantitative evaluation of midbrain atrophy may be useful in differentiating progressive supranulear palsy (PSP) from Parkinson disease (PD); however, this finding is not specific of PSP, and quantitative measurements are not always practical. We determined whether an abnormal superior midbrain profile (flat or concave aspect) is a more practical diagnostic parameter for PSP. METHODS: MR imaging studies of 25 patients with PSP and 27 with PD were reviewed by means of five parameters: midbrain superior profile on midsagittal T1-weighted images, midbrain atrophy, tegmental abnormal T2 hyperintensity, abnormal T2 putaminal hypointensity or hyperintensity on axial proton density–weighted images. We also measured the anteroposterior diameter of the midbrain on axial T2-weighted sections at the level of the superior colliculus. RESULTS: The finding of an abnormal superior profile of the midbrain had 68% sensitivity and 88.8% specificity. Midbrain atrophy had 68% sensitivity and 77.7% specificity. Tegmental T2 hyperintensity had 100% specificity but poor sensitivity (28%). Only 14.8% of patients with PD and 24% of those with PSP had abnormal putaminal T2 hypointensity; none had proton-density hyperintensity. With PSP, the average midbrain diameter was smaller than that with PD, but an important overlap was observed. Reader discordance was lower for the midbrain superior profile sign (eight of 52 cases); this was similar for tegmental hyperintensity (nine of 52 cases) and higher for midbrain atrophy (16 of 52 cases). CONCLUSION: An abnormal superior profile of the midbrain facilitates the distinction of PSP from PD and may support the clinical differential diagnosis of parkinsonism.